PERSEPSI MASYARAKAT KABUPATEN TANGERANG TERHADAP PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) - Muhammad Nur Fadillah; Taufiqqur rachman (JURNAL MITRA MANAJEMEN, 2020)
AbstractThe increasingly widespread development of Financial Technology in Indonesia also impacts Tangerang Regency, Banten, which is only 30 Km from DKI Jakarta. This development has influenced the perception of the Tangerang Regency community on the use of fintech, from the simple use for shopping to the fulfillment of lending needs. Fintech users in the Regency in this study were dominated by productive age groups ranging from late adolescence, early adulthood and late adulthood. The tangerang district's perception of fintech is built with a positive attitude of acceptance, motivated to use it, even has a strong interest in studying it further, most have positive experience with fintech although there are some criticisms of the use of fintech related to security, technical use and support services fintech which is not optimal. Keywords: Perception; Tangerang Regency; Fintech